FAKTOR FAKTOR MOTIVASI EKSTERNAL YANG MEMPENGARUHI PERAWAT DALAM PENGGUNAAN HANDSCOON STERIL DALAM PERAWATAN LUKA DI RUANG BEDAH RSUD PANEMBAHAN SENOPATI BANTUL - Hidayat, Nur (STIKES Wira Husada Yogyakarta, 2016)
ABSTRACT Background: In applying universal precautions one of them is to use sterile handscoon in wound care. The use of sterile handscoon in wound care is not optimal, because there are nurses who use clean handscoon during wound care. Objective: To determine the external factors affecting the motivation nurse on using sterile handscoon to wound care in the surgery room Panembahan Senopati Bantul Hospital. Methods: This study is quantitative research and survey method with cross sectional analytic. The population of this study were nurses in Melati and Bougenvil. The sampling technique has been using accidental sampling, with 22 nurses. Tool data collection has been using questionnaires and observation. Data has been using chi square. Results: The results showed the value of bivariate analysis using chi square formula are rewards factors (p=0,263), environmental factors (p=0,674), time factors (p=0,211) and nurses performance factors (p=0,604). This suggests that factors external motivation does not affect the nurse on using sterile handscoon to wound care. Conclusions: Rewards factors, environmental factors, time factors and performance factors work nurses do not affect external motivating factors of nurse on using sterile handscoon to wound care in the surgery room Panembahan Senopati Bantul Hospital. Keywords: External Motivation, Use of Sterile Handscoon